2016
DOI: 10.1039/c6mt00055j
|View full text |Cite
|
Sign up to set email alerts
|

X-ray fluorescence microscopic measurement of elemental distribution in the mouse retina with age

Abstract: The biologically important metals such as zinc, copper and iron play key roles in retinal function, yet no study has mapped the spatio-temporal distribution of retinal biometals in healthy or diseased retina. We investigated a natural mouse model of retinal degeneration, the Cln6 mouse. As dysfunctional metabolism of biometals is observed in the brains of these animals and deregulated metal homeostasis has been linked to retinal degeneration, we focused on mapping the elemental distribution in the healthy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…The suppression in bile acid metabolism during early recovery from profound FDM highlights the importance of maintaining energy metabolism in myopia. The GSEA findings provide supporting evidence for the RIDE model as well as complementing earlier biometric and ultrastructural findings showing that form-deprivation occlusion leads to changes in eye volume, refraction, thinning of the retina and choroid, and morphological evidence for hyperosmolarity ( Brocker, Thompson & Vasiliou, 2012 ; Crewther et al, 2006 ; Grubman et al, 2016 ; Hollborn et al, 2017 ; Junghans et al, 1999 ; Liang et al, 1995 ; Liang et al, 2004 ). Although a combination of posterior ocular tissue have been analysed in previous transcriptome studies on refractive errors ( McGlinn et al, 2007 ; Rada & Wiechmann, 2009 ; Riddell et al, 2016 ; Shelton et al, 2008 ; Stone et al, 2011 ), commonalities in differentially expressed genes have now been identified regardless of species, tissue analysed and genomic platform ( Riddell & Crewther, 2017a ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The suppression in bile acid metabolism during early recovery from profound FDM highlights the importance of maintaining energy metabolism in myopia. The GSEA findings provide supporting evidence for the RIDE model as well as complementing earlier biometric and ultrastructural findings showing that form-deprivation occlusion leads to changes in eye volume, refraction, thinning of the retina and choroid, and morphological evidence for hyperosmolarity ( Brocker, Thompson & Vasiliou, 2012 ; Crewther et al, 2006 ; Grubman et al, 2016 ; Hollborn et al, 2017 ; Junghans et al, 1999 ; Liang et al, 1995 ; Liang et al, 2004 ). Although a combination of posterior ocular tissue have been analysed in previous transcriptome studies on refractive errors ( McGlinn et al, 2007 ; Rada & Wiechmann, 2009 ; Riddell et al, 2016 ; Shelton et al, 2008 ; Stone et al, 2011 ), commonalities in differentially expressed genes have now been identified regardless of species, tissue analysed and genomic platform ( Riddell & Crewther, 2017a ).…”
Section: Discussionsupporting
confidence: 83%
“…Previous ultrastructural studies of form-deprivation in chick have demonstrated morphological abnormalities in photoreceptor outer segments, retinal pigment epithelium (RPE) nuclei, mitochondria and basal laminae ( Beresford, Crewther & Crewther, 1998 ; Liang et al, 1995 ; Liang et al, 2004 ; Liang et al, 1996 ) similar to those described elsewhere as characteristic of AMD ( Datta et al, 2017 ), CNV ( Ohno-Matsui et al, 2017 ) and glaucoma ( Kim & Park, 2017 ). These morphological changes occur concomitantly with elemental microanalytical evidence of hyperosmotic changes in ion distribution patterns across the retina, RPE and choroid ( Crewther et al, 2006 ; Grubman et al, 2016 ; Hollborn et al, 2017 ; Junghans et al, 1999 ; Liang et al, 1995 ; Liang et al, 2004 ) and reminiscent of physiologically induced hyperosmotic and oxidative stress elsewhere in the brain ( Brocker, Thompson & Vasiliou, 2012 ; Morland, Pettersen & Hassel, 2016 ; Veltmann et al, 2016 ). Indeed, oxidative stress has been suggested to contribute to the underlying mechanisms involved in profound myopia pathology ( Francisco, Salvador & Amparo, 2015 ).…”
Section: Introductionmentioning
confidence: 93%
“…The suppression in bile acid metabolism during early recovery from profound FDM highlights the importance of maintaining energy metabolism in myopia. The GSEA findings provide supporting evidence for the RIDE model as well as complementing earlier biometric and ultrastructural findings showing that form-deprivation occlusion leads to changes in eye volume, refraction, thinning of the retina and choroid, and morphological evidence for hyperosmolarity (Brocker et al 2012;Crewther et al 2006;Grubman et al 2016;Hollborn et al 2017;Junghans et al 1999;Liang et al 1995;Liang et al 2004). Manuscript to be reviewed Stone et al 2011), commonalities in differentially expressed genes have now been identified regardless of species, tissue analysed and genomic platform (Riddell & Crewther 2017a).…”
Section: Discussionsupporting
confidence: 70%
“…2017), CNV (Ohno-Matsui et al 2017) and glaucoma (Kim & Park 2017). These morphological changes occur concomitantly with elemental microanalytical evidence of hyperosmotic changes in ion distribution patterns across the retina, RPE and choroid (Brocker et al 2012;Crewther et al 2006;Grubman et al 2016;Hollborn et al 2017;Junghans et al 1999;Liang et al 1995;Liang et al 2004) and reminiscent of physiologically induced hyperosmotic and oxidative stress elsewhere in the brain (Brocker et al 2012;Morland et al 2016;Veltmann et al 2016). Indeed, oxidative stress has been suggested to contribute to the underlying mechanisms involved in profound myopia pathology (Francisco et al 2015).…”
mentioning
confidence: 97%
“…The nominal sample composition and thickness estimate is used to provide a first-order self-absorption correction, and inaccuracies have negligible impact on the quantitative concentrations of the first-row transition metals in these thin tissue sections, as reported by several groups. [83][84][85] Lighter element such as S and P are presented for distributional purposes only; absolute quantification of these elements is difficult and subject to significant errors from the assumption of matrix composition, thickness and density. Quantitative data were extracted as tiff files of quantitative per-pixel elemental area density in ng cm À2 , which were then imported into ImageJ v1.48, as described previously.…”
Section: Synchrotron Imagingmentioning
confidence: 99%